Older people, medication safety, and the role of the community pharmacist: a longitudinal ethnographic study. (21st November 2022) - Collier, Aileen; Balmer, Deborah; Dai, Linda; Hikaka, Joanna; Bloomfield, Katherine; Boyd, Michal
Abstract: Background: Older people with frailty and multimorbidity are at high risk of problematic polypharmacy. Community pharmacists have a key role in medication safety for older people. Aim: The aim of this study was to investigate the perspectives of older people with frailty, multimorbidity, and polypharmacy, and their family caregivers or whānau on the role of community pharmacists, including in situ pharmacist care practices. Method: This study was part of a larger video reflexive ethnography (VRE) study to explore medication safety and wellbeing for older people with frailty across care transitions including hospital, home, aged residential care, primary care, and outpatient care. This paper reports data from the interview, participant observation, and filming phases of the study. Results: Community pharmacists play a significant role in the medication safety of older people with frailty and polypharmacy. Analysis resulted in three main themes: (1) the older person–determined role of the pharmacist, (2) the 'taken for granted' safety work of the pharmacist, and (3) collective agency and medication safety. Conclusion: In circumstances where older people and their family caregivers or whānau had a trusted relationship with a community pharmacist, the pharmacist played a key role as mediator of medication safety and was central to older people's care. This key role as a member of the multidisciplinary team in the care of older people with frailty and multimorbidity should be better recognised and legitimised by clinicians and policy makers and resourced accordingly.